Numerical simulation of unsteady ethylene glycol/CNTs micropolar nanofluid flow through a squeezing channel: An approach to industrial applications. Issue 6 (31st March 2022) - Sastry, D. R. V. S. R. K.; Naresh Kumar, N.; Shaw, Sachin
Abstract: The impressive high thermal conductivity and low weight allow the carbon nanotubes (CNTs) to improve heat dissipation and cooling. In the present problem, we aim to analyze the CNTs embedded micropolar nanofluid flow between two parallel stretching sheets with the base fluid ethylene glycol (EG) which is effectively used as antifreeze and coolant. Both single‐walled carbon nanotubes and multiwalled carbon nanotubes (MWCNTs) are considered. The fluid is influenced by the external magnetic field parallel to the microrotation along with viscous and Joule dissipations. The flow and heat equations are converted to a set of coupled ordinary differential equations with the aid of similarity transformations. Due to the nonexistence of the closed‐form solution, we have developed the analytical approximate solution by homotopy analysis method using the polynomial base function. Furthermore, we have used the most efficient Runge–Kutta integration scheme of the fourth order associated with shooting technique to solve the system of equations. Results are exhibited graphically for various physical parameters and also found a good agreement with earlier work. From the results, we noticed that squeezing increases the angular velocity of the fluid particles. Also, in the case of squeezing, the volume fraction has enhanced the viscous drag and was found high for MWCNT–EG nanofluid.